High precision tests of QED Measurement of the alpha-particle and helion rms charge radius and the transition energies in highly-charged ions - Machado, Jorge Felizardo Dias Cunha (2018)
This work aims to provide insight on Bound-State Quantum-Electrodynamics (BSQED) by experimental fundamentals high-precision tests in exotic states of matter. Although BSQED and the relativistic many-body problem have been undergoing important progress, there are still some issues that require the increase of the number and accuracy of experimental fundamental tests. The first part of this work was done within the framework of the recent experiment in muonic helium ions ( 4He+ and 3He+) by the CREMA collaboration. This experiment, aims to provide new accurate values for the root-mean-square (rms) charge radii of the helium isotopes nuclei that are extracted from the measurement of the Lamb Shift, i.e., the measurement of the energy difference between the 2S 2P states. With the goal of measuring the transition energies with an accuracy of at least 50 ppm, the rms charge radii of the helium isotopes will be determined with an uncertainty of 0.03%, a factor of ten more precise than previous results obtained from electron scattering. The second part of this work aims the high-precision measurement of x-ray transitions in Highly-Charged Ions (HCI) using a Double-Crystal Spectrometer (DCS). These ions were produced in the plasma of an Electron-Cyclotron Resonance Ion Source (ECRIS). This kind of spectrometer is able not only to provide high-precision measurements but also reference-free measurements, without reference to any theoretical or experimental energy. Four transitions energies from n = 2!n = 1 have been measured in an argon plasma in three different charge states, He-, Be- and Li-like, with an accuracy of better than 3 ppm. Besides the energies, the natural width of each transition has also been experimentally obtained. The obtained results are in excellent agreement with the most recent theoretical calculations.